Functional characterization of three cDNA libraries from the diploid wheat Triticum monoccocum (AmAm) with different growth habits - Diaz, M. (2011)
The diploid wheat Triticum monococcum (2n = 2x = 14, A mA m) constitutes an excellent and simplified model to study wheat genome expression since it has lower genome complexity compared to polyploid wheat species.The analysis of a collection of near 10,000 ESTs obtained from two libraries of T. monococcum (TM011XXX and TM043E1X) and one from T. monococcum ssp. aegilopoides (TM046E1X), lead to 2246, 1843 and 2405 unigenes, respectively. The unigenes from each library were individually analyzed through the Blast2Go interface revealing higher identity compared to EST databases. However, a low percentage of sequences showed significant similarity with Triticum databases, reflecting that several novel Triticum expressed genes have been identified in these libraries. The sequences annotation and classification under GO categories showed similar distribution for the three libraries, but differences were identified in some subcategories.When a virtual unique library was constructed including the sequences from the three libraries, seventeen genes were found to be over-expressed between reproductive and vegetative tissues and thirty-five showed genotype-specific expression. These differentially expressed genes included several regulatory proteins and some unreported sequences. Some of these differentially expressed genes were validated by qRT-PCR. The exploration for specific polymorphisms allowed the identification of several SNPs.These EST libraries constitute a valuable tool for the assessment of active metabolic pathways in vegetative and reproductive tissues in diploid wheat species. A more detailed assessment of expression profiles of genotypes with spring and winter growth habits would allow the identification of the transcriptomic strategies developed under the pressure of these antagonistic growth conditions.